Private Handwritten Prayer Books of the Catholics from the XVIII–XIX-century Right-Bank Ukraine as an Evidence of the Era). - Путова, Ганна Вадимівна (Poznańskie Studia Slawistyczne, 2018)
The article presents a description and analysis of the peculiarities of the handwritten prayer books of Catholics of the Right-Bank Ukraine of the XVIІІ–XIX centuries on the example of one of the collections of the Central State Historical Archives of Ukraine in Kiev.